2017
DOI: 10.1051/matecconf/201710812001
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the dynamic characteristics of a complex jointed structure

Abstract: Abstract. Every structure that assembled with the joints has a significant effect on the dynamic behaviour of the structure. Therefore, the overall dynamic behaviour of the jointed structure highly relies on these joints. Finite element method (FEM) is commonly used to model an element connector for the jointed structure due to its because every jointed structure has its owns joint properties. The aims of this research are to identify the potential element connectors that are available in commercial finite ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Its shows that mode shape in Table 3 are in good agreement with experimental counterpart compared with the mode shapes in Table 2 as agreed in the MAC values shows in Table 1. Previous studies have suggested that the predicted mode shapes with MAC values above 0.70 can be acceptance as in good correlation [5].…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Its shows that mode shape in Table 3 are in good agreement with experimental counterpart compared with the mode shapes in Table 2 as agreed in the MAC values shows in Table 1. Previous studies have suggested that the predicted mode shapes with MAC values above 0.70 can be acceptance as in good correlation [5].…”
Section: Resultsmentioning
confidence: 82%
“…Computerised analysis packages such as the finite element method is found to be more beneficial in predicting the dynamic behaviours of the structure [5]. However, it is difficult and complicated to model the welds itself because of non-linearity effects due to the welding process such as residual stress that are complex and influenced by many uncertain parameters [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These data are then compared to finite element analysis results so as to identify the degree of correlations between them. However, before the experiment is conducted, several factors, such as frequency bandwidth, suspension orientation, excitation method and number of accelerometers need to be considered from finite element analysis [35][36][37].…”
Section: Finite Element Modelling Proceduresmentioning
confidence: 99%